Italian iced - Logan, Kylie (Logan, Kylie. Ethnic eats mysteries., 2018)
"When Laurel Inwood features Italian cuisine on the Terminal at the Tracks menu, she knows she'll need to stock the shelves, the fridge, and the freezer with plenty of wonderful delicacies. She just never expected one of them to be her former employer, Hollywood superstar Megan Cohan. And one day, when Laurel is at the the restaurant early to get ready for the regular rush of customers, that's exactly what she finds - Meghan dead in the Terminal freezer. What's a Hollywood A-lister doing in Hubbard, Ohio? For Laurel, that's the real question, because the first question she'd ask in any other murder investigation - who would want the victim dead? - seems pretty much a no-brainer in this case. Who would want Meghan dead? Just about anybody who had ever met her."--Page [4] of cover.